2003
DOI: 10.1128/iai.71.8.4278-4288.2003
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Expression of Inflammatory Cytokines and Chemokines at Early Stages of Infection withLeishmania amazonensis

Abstract: Infection of mice with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
181
2
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 153 publications
(209 citation statements)
references
References 56 publications
20
181
2
5
Order By: Relevance
“…Although IL-10-deficient mice were more resistant to L. major (Brooks et al, 2006;Kane and Mosser, 2001), deletion of the IL-10 gene did not change the susceptibility of mice to La parasites (Jones et al, 2002), suggesting to us that an IL-10-independent mechanism in persistent infection is caused by La infection. Accordingly, this study supports the view that amastigotes in the L. mexicana complex (La, L. mexicana, and L. pifanoi) can directly suppress the activation and/or accelerate the degradation of signaling pathways via their peptidases/ proteinases (Cameron et al, 2004), and that this delayed and suppressed DC activation is responsible for impaired innate and acquired immunity to parasite infection (Ji et al, 2003;Xin et al, 2007).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Although IL-10-deficient mice were more resistant to L. major (Brooks et al, 2006;Kane and Mosser, 2001), deletion of the IL-10 gene did not change the susceptibility of mice to La parasites (Jones et al, 2002), suggesting to us that an IL-10-independent mechanism in persistent infection is caused by La infection. Accordingly, this study supports the view that amastigotes in the L. mexicana complex (La, L. mexicana, and L. pifanoi) can directly suppress the activation and/or accelerate the degradation of signaling pathways via their peptidases/ proteinases (Cameron et al, 2004), and that this delayed and suppressed DC activation is responsible for impaired innate and acquired immunity to parasite infection (Ji et al, 2003;Xin et al, 2007).…”
Section: Discussionsupporting
confidence: 85%
“…However, we and others have found that La infection results in nonhealing disease in most inbred mouse strains due to the induction of a weak, Th1/Th2 mixed response (Ji et al, 2002;Jones et al, 2000). The deficient Th1 response seen in La-infected mice is due largely to profound, multiple impairments in numerous cytokines, chemokines, and their corresponding receptors at an early stage of the infection (Ji et al, 2003). Our recent evidence of intrinsic defects in La-infected DCs support the concept that Leishmania parasites can manipulate the immune response at the APC level (Xin et al, 2007).…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations